2020
DOI: 10.3390/catal10111279
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Glycerol Catalytic Valorization: A Review

Abstract: Once a biorefinery is ready to operate, the main processed materials need to be completely evaluated in terms of many different factors, including disposal regulations, technological limitations of installation, the market, and other societal considerations. In biorefinery, glycerol is the main by-product, representing around 10% of biodiesel production. In the last few decades, the large-scale production of biodiesel and glycerol has promoted research on a wide range of strategies in an attempt to valorize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 283 publications
(298 reference statements)
0
73
0
1
Order By: Relevance
“…A preliminary benchmark test was carried out with the initial conditions that corresponded to those evaluated in previous investigations carried out in our laboratory [5]. These conditions corresponded to a 0.3 M glycerol solution, a reaction temperature of 60 °C, 5 bar of oxygen, 0.5 g of catalyst, and a NaOH/glycerol molar ratio of 4.…”
Section: Experimental Tests and Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary benchmark test was carried out with the initial conditions that corresponded to those evaluated in previous investigations carried out in our laboratory [5]. These conditions corresponded to a 0.3 M glycerol solution, a reaction temperature of 60 °C, 5 bar of oxygen, 0.5 g of catalyst, and a NaOH/glycerol molar ratio of 4.…”
Section: Experimental Tests and Optimizationmentioning
confidence: 99%
“…Different glycerol valorization pathways have been studied to generate alternative energy carriers and to obtain high-value-added compounds of interest in different industrial applications, such as food, cosmetics, paints, and pharmaceuticals, among others [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier before, Corma reported that glyc-Figure 3. Reaction Mechanism for production of 1,2-Propanediol (1,2-PDO) [94]. erol dehydration at temperature 350 °C and 500 °C takes place in two pathways and declared that 66% will be directed to the formation of acetol and 33% towards acrolein.…”
Section: In-depth Knowledge On Reaction Mechanism and Thermodynamicsmentioning
confidence: 99%
“…Furthermore, the latter market is unable to sustain the increasing availability of glycerol. The development of glycerol transformation routes that have a large potential volume of production and do not require heavy purification of the feed is envisaged and, among these, the production of hydrogen by steam reforming appears promising [ 11 ].…”
Section: Introductionmentioning
confidence: 99%